Clocks, scales & measurements - Robson, Pam. (New York : Gloucester Press, 1993)
Presents information and activities related to the measurement of time, weight, area, density, and other aspects of the world around us.
Includes index.
Keywords: Physical instruments -- Juvenile literature; Physical measurements -- Experiments -- Juvenile literature; Measurement -- Experiments; Experiments